2012
DOI: 10.1155/2012/916306
|View full text |Cite
|
Sign up to set email alerts
|

Asystole following Reintubation during Suspension Laryngoscopy

Abstract: Transient increase in heart rate and mean arterial pressure commonly occur during manipulation of the airway via direct laryngoscopy. This phenomenon is understood to be due to a sympathetic nervous system reflex causing an increase in plasma catecholamines. Rarely, severe bradycardia and possible asystole can occur following laryngoscopy. One previous report described asystole during suspension laryngoscopy after uneventful direct laryngoscopy. Here we report a case of asystole occurring at the time of reinse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…The laryngeal surface of the epiglottis is innervated by a general sensory branch of the vagus nerve: the internal branch of the superior laryngeal nerve . Alternatively, it has been proposed that stimulation of this nerve may trigger an efferent parasympathetic vagal response to the sinoatrial node of the heart, which decreases conduction and results in significant bradycardia . However, in our case, placement of the laryngoscope on the laryngeal surface of the epiglottis without tension was insufficient to trigger bradycardia.…”
Section: Discussionmentioning
confidence: 59%
“…The laryngeal surface of the epiglottis is innervated by a general sensory branch of the vagus nerve: the internal branch of the superior laryngeal nerve . Alternatively, it has been proposed that stimulation of this nerve may trigger an efferent parasympathetic vagal response to the sinoatrial node of the heart, which decreases conduction and results in significant bradycardia . However, in our case, placement of the laryngoscope on the laryngeal surface of the epiglottis without tension was insufficient to trigger bradycardia.…”
Section: Discussionmentioning
confidence: 59%
“…One of the proposed mechanisms is that, during suspension laryngoscopy, the stimulus is on the laryngeal surface of the epiglottis, which differs from the vallecular stimulation by curve laryngoscopy for orotracheal intubation. Sensory innervation of the laryngeal surface of the epiglottis is mainly attributed to the internal branch of the superior laryngeal nerve, derived from the vagus nerve, and its intense stimulation may predispose asystole [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…As a prophylactic strategy, the routine use of atropine before laryngoscopy is already implemented in the pediatric population, in which intense vagal reflex is well described [14]. Adult patients submitted to suspension laryngoscopy may also benefit from the use of vagolytic drugs at the beginning of the surgical procedure, especially from high vagal tone, identified in the cardiologic evaluation [9]. As another proposal, it is suggested that deep anesthesia associated with topical lidocaine may reduce the risk of asystole, but data are still limited [15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, she was given vagotonic agents, which included propofol, remifentanil, and succinylcholine. Remifentanil is known to reduce sympathetic activity from the central nervous system, 5,6 and succinylcholine causes stimulation of the muscarinic receptors in the sinoatrial node to cause bradycardia. 7 The data are sparse on systematic trials investigating this rare occurrence, but limited data suggest that topical lidocaine and deep anesthesia may decrease the likelihood of asystole after direct laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%